2009
DOI: 10.1007/s10661-009-0960-3
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of nitrogen dioxide into ozone and prediction of ozone concentrations using multiple linear regression techniques

Abstract: Analysis and forecasting of air quality parameters are important topics of atmospheric and environmental research today due to the health impact caused by air pollution. This study examines transformation of nitrogen dioxide (NO(2)) into ozone (O(3)) at urban environment using time series plot. Data on the concentration of environmental pollutants and meteorological variables were employed to predict the concentration of O(3) in the atmosphere. Possibility of employing multiple linear regression models as a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 5 publications
4
63
1
2
Order By: Relevance
“…However, bright sunshine hours were positively and significantly correlated with t ambient NO 2 concentrations and negatively with SO 2 concentrations. Although the ambient NO 2 and hours of bright sunshine were positively correlated with each other in the current study, Logan et al, (1981); Thompson (1992) and Ghazali et al, (2009) have shown that a considerable amount of NO 2 is converted to O 3 through photochemical reactions in the presence of sunlight. Similarly, the same correlation was observed by Trebs et al in 2009. The diversity and abundance of lichens are considered as indicators of environmental quality, where high values correspond to good air quality (Asta et al, 2002a(Asta et al, , 2002b.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…However, bright sunshine hours were positively and significantly correlated with t ambient NO 2 concentrations and negatively with SO 2 concentrations. Although the ambient NO 2 and hours of bright sunshine were positively correlated with each other in the current study, Logan et al, (1981); Thompson (1992) and Ghazali et al, (2009) have shown that a considerable amount of NO 2 is converted to O 3 through photochemical reactions in the presence of sunlight. Similarly, the same correlation was observed by Trebs et al in 2009. The diversity and abundance of lichens are considered as indicators of environmental quality, where high values correspond to good air quality (Asta et al, 2002a(Asta et al, , 2002b.…”
Section: Discussioncontrasting
confidence: 62%
“…According to Rondon and Granat (1994), NO 2 also enters via the cuticle of leaves without internal resistance. The lower NO 2 concentrations at the HPNP might also be due to the conversion process, in which ambient NO 2 converts into O 3 in the presence of sunlight (Ghazali et al, 2009). In addition to individual effects, a combination of above factors may also have contributed to the low levels of NO 2 and SO 2 at HPNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalam kajian terkini di Malaysia, siri masa ozon sering diramal menggunakan kaedah rangkaian neural dan model regresi linear berganda; contohnya, Ghazali et al (2010), Muhamad et al (2015) dan Tan et al (2016). Proses peramalan melalui kedua-dua kaedah adalah bergantung kepada faktor cuaca seperti suhu, kelembapan, radiasi dan kelajuan angin solar serta faktor-faktor gas seperti gas pelopor metana (CH 4 ), karbon monoksida (CO) dan nitrogen oksida (NO x ).…”
Section: Pengenalanunclassified
“…Several researchers have demonstrated through data, the existence of a correlation between seasonal trends in the level of ozone concentrations are the local surroundings of various monitoring stations (Adeeb and Shooter 2004;Duenas et al, 2004;Feng et al, 2005;Lee et al, 2009;Piikki and Klingberg, 2009;Azmi et al, 2010). The trend analysis of ozone always has maintained a relationship with the trends of VOC, NO and NOx in both urban and suburban areas (Atkinson, 2000;Ghazali et al, 2010;Keuken et al, 2009;Martin et al, 2009;Milt et al, 2009). Local concentrations of ozone are reduced in the vicinity of heavy vehicular traffic as a results of ozone scavenging by NO and NO 2 (Atkinson, 2000;Ahammed et al, 2006;Tu et al, 2007;Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 98%